Time course of contrast enhancement patterns after Gd-BOPTA in correlation to myocardial infarction and viability: a feasibility study. - Sandstede, J; Beer, M; Lipke, C; Pabst, T; Kenn, W; Harre, K; Neubauer, S; Hahn, D (2001)
Our objective was to analyze contrast enhancement patterns (CEP) and their time course after myocardial infarction (MI) following injection of Gd-BOPTA in correlation with recovery of regional function. Seven patients with subacute MI (18 +/- nine days) were examined before, as well as three and six (n = six) months after, revascularization of the infarct-related artery. Regional wall motion abnormalities were assessed by cine-MRI, and repetitive images of one representative slice were acquired up to 45 minutes after 0.05 mmol/kg Gd-BOPTA using a T1-w TSE-sequence. Two patients showed mid-wall/subendocardial, one patient subendocardial enhancement of MI associated with mechanical improvement after revascularization. Three patients without improvement revealed a mid-wall hypoenhanced zone within the first five minutes after injection, which was unchanged at follow-up. One patient with partial functional improvement showed transmural enhancement and a mid-wall hypoenhanced zone in adjacent areas. With this feasibility study, we concluded that mid-wall and/or subendocardial enhancement after Gd-BOPTA was associated with viable myocardium, whereas detection of microvascular obstruction correlating with scar formation is suggested by mid-wall hypoenhancement within the first five minutes after injection.